Cultural code in sports: definition, functions, types and categories - Manziuk E.V. ,; Melnikova N.Yu. ,; Leontieva N.S. ,; Koreneva M.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study – to substantiate and formulate the term “cultural code in sports”, define its functions, and also identify the relationship between its types and categories. Methods and structure of the study. In the course of the research, the following methods were applied: general (collection and analysis of scientific research and the available source base on the problem under consideration), general logical (generalization, comparison, analogy, comparison, systematization, etc.). Results and conclusions. The authors indicate that the cultural code in sports is a multifunctional system. The following functions have been identified and defined: accumulative, diplomatic, identification, image, integrative, communicative, cognitive, aesthetic, which are responsible for preserving the ideals and values of sports, creating a favorable friendly atmosphere in the sports arena, and are aimed at uniting people for the implementation of cultural interaction. Based on the system analysis of the totality of components of the cultural code, a structure of the relationship between the types and categories of the cultural code in sports has been developed.